1977
DOI: 10.1099/00221287-100-1-139
|View full text |Cite
|
Sign up to set email alerts
|

Phage Receptor Material in Lactobacillus casei

Abstract: S U M M A R YIn Lactobacillus casei s-I , D-galactosamine and L-rharnnose comprised a phage receptor for phage J-I. A mixture of D-galactosamine and L-rhamnose effectively inactivated phage J-I, and a J-[-resistant mutant strain, L . casei S-I/J-I, lacked D-galactosamine in its surface component. The phage-inactivating effects of D-galactosamine and L-rhamnose were strongly dependent on the concentration of each substance and on temperature.It is suggested that the receptor for phage J-I involves both D-galact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…The uniform distribution of fluorescence suggests the ligands for gp16 binding are not localized in any particular part of the cell but regularly distributed on the cell surface. These observations are consistent with J-1 and PL-1 recognizing saccharide-containing receptors within the outer layer of the cell wall, including a role for L-rhamnose as noted previously (67)(68)(69).…”
Section: Resultssupporting
confidence: 79%
“…The uniform distribution of fluorescence suggests the ligands for gp16 binding are not localized in any particular part of the cell but regularly distributed on the cell surface. These observations are consistent with J-1 and PL-1 recognizing saccharide-containing receptors within the outer layer of the cell wall, including a role for L-rhamnose as noted previously (67)(68)(69).…”
Section: Resultssupporting
confidence: 79%
“…In experiments 1 to 3, we observed that the PROB culture was significantly more effective at reducing cecal Salmonella Enteritidis than the LAB3 culture. This demonstrates that all lactic acid bacteria are not equally effective at reducing enteric salmonellosis in poultry, as has been described previously (Yokokura, 1997;Kim et al, 2006). Slight differences in surface protein expression between lactobacilli could help describe just one of the possible differences between lactic acid bacteria that effectively prevent enteric infections and those bacteria that confer no protection.…”
Section: Resultsmentioning
confidence: 63%
“…O-acetylation of the lipopolysaccharide side chains, changes in the bonding between the lipopolysaccharide trisaccharide units from a1A4 to b1A4) on the host cell, resulting in the inability of the cell to adsorb additional phage. Although the previous examples of phage receptor modification involve Gram-negative bacteria, it is possible that a similar phenomenon may occur in E. faecalis as the phage receptors in most Gram-positive, low G+C bacteria are cell surface polysaccharides (Vidaver & Brock, 1966;Douglas & Wolin, 1971;Cleary et al, 1977;Yokokura 1977;Keogh & Pettingill, 1983;Valyasevi et al, 1990;Schäfer et al, 1991). If this is the case, then evolutionarily speaking, it may be that originally E. faecalis TUSoD11 was nonlysogenic and possessed cell-surface phage receptors.…”
Section: Discussionmentioning
confidence: 99%